If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12n-3=69
We move all terms to the left:
-12n-3-(69)=0
We add all the numbers together, and all the variables
-12n-72=0
We move all terms containing n to the left, all other terms to the right
-12n=72
n=72/-12
n=-6
| 0.3(x+50)-6=0.4(3x+20) | | x/2+9=2x+5 | | x2( | | 3^(t-1)=10 | | x2( | | 20)8x+5=21 | | 3^t-1=10 | | -5x-2x=56 | | (4-v)(3v-5)=0 | | -w/9=-2 | | 2(x-3)+3(x-1)=5x+4(x-4) | | 8=18=3/8(16-40n) | | 28.05=5g+3.65 | | m+1=-7m+9 | | 3(2a+5)+2(3-a)a=4= | | 9–9x=0 | | 6x-10=2(-3x-5) | | 2x-6=18=x=45 | | 288=172-v | | 4x+2(-1.3x-1)=-2 | | p+(-23)=-14 | | -9+s=17 | | -3(4x+4)+6=-6-12x | | m-(-21)=9 | | 2(2.8x-4.6)-x=-4 | | (2x+9)=17. | | n+(-5)=27 | | S=(3x+8)(4x-1)-12x²-29x-8 | | 4(3x-1)-6(2x+5)=4x+14 | | j+13=-27 | | 2-5k=37 | | g+27=8 |